Newtonian heating effect on heat absorbing unsteady MHD radiating and chemically reacting free convection flow past an oscillating vertical porous plate - Prabhakar Reddy, Bijjula; Makinde, Oluwole D. (Zielona Góra: Uniwersytet Zielonogórski)
In this article, we have discussed in detail the effect of Newtonian heating on MHD unsteady free convection boundary layer flow past an oscillating vertical porous plate embedded in a porous medium with thermal radiation, chemical reaction and heat absorption. The governing PDEs of the model together with related initial and boundary conditions have been solved numerically by the finite element method.
Keywords: Newtonian heating; radiation parameter; chemical reaction rate; oscillating plate; heat absorption parameter